Two Cases of Allergic Fungal Sinusitis with Differing Postoperative Course - Yuma Matsumoto; Hidenori Yokoi; Michitsugu Kawada; Masachika Fujiwara; Koichiro Saito (Case Reports in Otolaryngology)
Allergic fungal sinusitis (AFS) often develops in unilateral paranasal sinuses, which must be differentiated from tumors. When AFS develops on both sides, however, it must be differentiated from eosinophilic chronic sinusitis with evident eosinophilic infiltration at nasal/paranasal sinus mucosa; both conditions are highly recurrent and commonly considered intractable paranasal sinusitis. Surgical correction is the primary treatment method for AFS, as it is essential to connect the paranasal sinus communication to ensure exhaustive resection of the pathologic mucosa and for nasal steroids to reach each paranasal sinus. We recently encountered two AFS cases with differing postoperative courses. Case 1 showed evident exacerbation in the computed tomography findings, which suggests progression to eosinophilic sinusitis. Case 2 showed a benign prognosis without recurrence. Close long-term follow-up should be mandatory after surgery for the treatment of AFS.